Arbetsterapautiska interventioner för vuxna med ADHD : En litteraturstudie - Palsson, Ewa (2015)
The purpose of this study was through careful examination of scientific articles examining the types of occupational therapy interventions available for adults with Attention Deficit Hyperactivity Disorder (ADHD). The method used for this study was a literature review. The choice of literature has consisted of scientific articles. To identify relevant literature, the search of the literature has been made in a number of different databases, including databases available at Luleå University of Technology. In total, seven scientific articles formed the basis for this study. The result shows that there are interventions available for adults with ADHD to facilitate everyday life. Four categories were identified: organization of the physical environment, try out technical means to facilitate and support in everyday life, teach strategies and support to facilitate everyday life and finally, support in social environments and in contact with the surroundings. Furthermore, the result shows a need for continued research on how interventions can be used in other problem areas of everyday life for adults with ADHD. Validerat; 20150623 (global_studentproject_submitter)